The long Q‐loop of Escherichia coli cytochrome bd oxidase is required for assembly and structural integrity. Issue 10 (13th February 2020) - Theßeling, Alexander; Burschel, Sabrina; Wohlwend, Daniel; Friedrich, Thorsten
Abstract : Cytochrome bd ‐I oxidase is a terminal reductase of bacterial respiratory chains produced under low oxygen concentrations, oxidative stress, and during pathogenicity. While the bulk of the protein forms transmembrane helices, a periplasmic domain, the Q‐loop, is expected to be involved in binding and oxidation of (ubi)quinol. According to the length of the Q‐loop, bd oxidases are classified into the S (short)‐ and the L (long)‐subfamilies. Here, we show that either shortening the Q‐loop of the Escherichia coli oxidase from the L‐subfamily or replacing it by one from the S‐subfamily leads to the production of labile and inactive variants, indicating a role for the extended Q‐loop in the stability of the enzyme. Abstract :